2014
DOI: 10.2174/1568026614666141203123620
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Lanthanides in the Free Radicals Homeostasis

Abstract: Lanthanides are group of rare-earth elements with growing applications both in the industry and healthcare. Their unique properties impose various possibilities for involvement in electron transfer reactions essential for the cellular survival and health on general. The intensified contact of people with lanthanides and the expanding medicinal applications of their compounds insist more profound knowledge on the involvement in biologically relevant electron transfer reactions. It is well known that the balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…The assignments and discussion of the H-Mef and the Na-Mef bands are consistent with literature [11]. The Gd(Mef) 3 assignment was found to be representative (see Table S3). In the cases of the other compounds, the band assignments were the same as that of gadolinium.…”
Section: Vibrational Spectroscopysupporting
confidence: 84%
See 3 more Smart Citations
“…The assignments and discussion of the H-Mef and the Na-Mef bands are consistent with literature [11]. The Gd(Mef) 3 assignment was found to be representative (see Table S3). In the cases of the other compounds, the band assignments were the same as that of gadolinium.…”
Section: Vibrational Spectroscopysupporting
confidence: 84%
“…The analytical and thermoanalytical (TG) data on the synthesized compounds is shown in Table 1. These results allowed us to establish the stoichiometry of these compounds, which is in agreement with the general formula Ln(Mef) 3 , where Ln represents trivalent lanthanides (Sm to Dy) and Mef is mefenamate. The thermoanalytical results showed that the compounds were obtained in their anhydrous state.…”
Section: Thermal Analysissupporting
confidence: 74%
See 2 more Smart Citations
“…15 REEs, including yttrium, have been biologically evaluated and proved for risk in inducing hypertension in housewives [9]. The possible explanation might be associated with the disturbance of REEs in redox balance, causing chronic oxidative stress damage and cell apoptosis [10]. Another theory may be related to their competition with those important nutritional ions, such as Ca 2+ , Zn 2+ , Mg 2+ , and Cu 2+ [11].…”
Section: Introductionmentioning
confidence: 99%